Zatoichi's Vengeance Based on a Short Story by Kan Shimozawa - Tanaka, Tokuzô; Miyagawa, Kazuo; Katsu, Shintaro; Amachi, Shigeru; Hamamura, Jun (Zatoichi: The Blind Swordsman Collection, 2019)
Zatoichi encounters a dying man, who asks the itinerant masseur to deliver a bag of money to his young son; he agrees to fulfill the request, finding the boy in a village terrorized by criminals. This is the first entry to scrutinize the swordsman's methods, as a blind monk confronts Zatoichi about his violent approach to problem solving and Zatoichi finds the child turning to the same bloodstained path. [www.criterion.com]